Detection of viral infections by innate immunity (2020)
Pattern recognition receptors (PRRs) and inflammasomes are a key part of the anti-viral innate immune system as they detect conserved viral pathogen-associated molecular patterns (PAMPs). A successful host response to viral infections critically depend on the initial activation of PRRs by viruses, mainly by viral DNA and RNA. The signalling pathways activated by PRRs leads to the expression of pro-inflammatory cytokines, to recruit immune cells, and type I and type III interferons which leads to the induction of interferon stimulated genes (ISG), powerful virus restriction factors that establish the “antiviral state” . Inflammasomes contribute to anti-viral responses through the maturation of interleukin (IL)-1 and IL-18 and through triggering pyroptotic cell death. The activity of the innate immune system along with the adaptive immune response normally leads to successful virus elimination, although disproportionate innate responses contribute to viral pathology. In this review we will discuss recent insights into the influence of PRR activation and inflammasomes on viral infections and what this means for the mammalian host. We will also comment on how specific PRRs and inflammasomes may be relevant to how SARS-CoV-2, the virus responsible for the current COVID-19 pandemic, interacts with host innate immunity.